2018
DOI: 10.3390/sym10060220
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal and Luminance Contrast Properties of Symmetry Perception

Abstract: Recent studies have shown that limiting the lifetime of pattern elements improves symmetry detection, potentially by increasing the number of element locations. Here, we investigate how spatial relocation, luminance contrast modulation and lifetime duration of elements affect symmetry perception in dynamic stimuli. Stimuli were dynamic dot-patterns containing varying amounts of symmetry about a vertical axis. Symmetrical matched-pairs were: (i) relocated to multiple successive, but random locations (i.e., mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
2
0
1
Order By: Relevance
“…Our results support behavioural [93][94][95][96] and recent neuroscienti c evidence 30,46,51,52 of global processes for symmetry representation. We propose that classic models 6,11,12,[20][21][22][23][24][25] , which emphasise early responses to pairwise correlations in the image, should be updated to consider the exibility of mechanisms for symmetry perception.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results support behavioural [93][94][95][96] and recent neuroscienti c evidence 30,46,51,52 of global processes for symmetry representation. We propose that classic models 6,11,12,[20][21][22][23][24][25] , which emphasise early responses to pairwise correlations in the image, should be updated to consider the exibility of mechanisms for symmetry perception.…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, in this study we found evidence of a representation of symmetry generated by the amodal completion of partially occluded symmetrical shapes. This adds to the recent literature showing that the representation of symmetry can exist in the brain at a non-retinotopic global level 30,46,51 (see also behavioural evidence [93][94][95][96] ). The amodal symmetry was indexed by a SPN-like response over extrastriate areas, in line with literature showing amodal completion is achieved at the level of LOC 56,57 .…”
Section: Discussionsupporting
confidence: 56%
“…Although a substantial number of natural objects are symmetric and the solid perceptual representation of symmetry has been reported ( Sharman and Gheorghiu, 2018 ; Sakai et al, 2021 ), only a fraction of V4 neurons showed significant tuning to symmetry in the present experiment. The limited spatial extent of the receptive filed might account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 58%